The Impact of Self-Esteem on Narcissistic Behavior Among Instagram-Active Students - Sabilah, Nurul Havifah; Syahputra, Yuda; Mulyadi, Mulyadi (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
This study aims to examine the effect of self-esteem on narcissistic tendencies among Instagram users at SMK Negeri 41 Jakarta. In the current digital era, social media platforms like Instagram play a crucial role in adolescents' lives, potentially influencing their self-perception and social interactions. This research employs a quantitative method with a survey design to identify and analyze the impact of self-esteem on narcissistic behavior among students using Instagram at SMK Negeri 41 Jakarta. Data were collected using a questionnaire from a population of 281 individuals, selected through random sampling techniques and the Slovin formula. The instrument used was a questionnaire adapted from relevant theses. Data analysis involved normality and linearity tests. The normality test results showed a sig. (2-tailed) value for self-esteem of 0.001 and for narcissism of 1.802. Since the Asymp. sig. (2-tailed) values for both self-esteem and narcissism are greater than 0.05, the data are normally distributed. Additionally, the linearity test showed an F (Linearity) value of 46.354, which is greater than 0.05, indicating a significant linear relationship between self-esteem (X) and narcissistic tendencies (Y).